1994
DOI: 10.1152/ajpregu.1994.267.2.r569
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of central vascular blood flow in the turtle

Abstract: The purpose of this study was to determine the effects of vagal nerve stimulation on the pulmonary and systemic circulations in the turtle Pseudemys scripta. The heart rate (HR), systemic vascular resistance (Rsys), pulmonary vascular resistance (Rpul), total pulmonary blood flow (Qpul), and total systemic blood flow (Qsys) were measured during electrical stimulation of the vagal efferent and the vagal afferent nerves. Vagal efferent nerve stimulation resulted in a bradycardia, increased Rsys and Rpul, and a 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 0 publications
7
31
0
Order By: Relevance
“…LAo, as previously verified (Comeau and Hicks, 1994;Wang and Hicks, 1996). Acoustic gel was infused between the blood vessels and flow probes to enhance the signal and the excised piece of the plastron was resealed in its original position using surgical tape and fast-drying epoxy resin.…”
Section: Surgical Proceduressupporting
confidence: 73%
See 1 more Smart Citation
“…LAo, as previously verified (Comeau and Hicks, 1994;Wang and Hicks, 1996). Acoustic gel was infused between the blood vessels and flow probes to enhance the signal and the excised piece of the plastron was resealed in its original position using surgical tape and fast-drying epoxy resin.…”
Section: Surgical Proceduressupporting
confidence: 73%
“…Likewise, systemic α-adrenergic tone mediates the increased peripheral vasoconstriction that occurs during diving in mammals and birds (Butler and Jones, 1971;Butler, 1982;Lacombe and Jones, 1991;Signore and Jones, 1995). In freshwater turtles, adrenergic fibres innervate the systemic circulation (Berger and Burnstock, 1979), and α-adrenergic stimulation increases Rsys in normoxic animals (Comeau and Hicks, 1994;Hicks and Farrell, 2000b;Overgaard et al, 2002). Anoxic exposure of turtles is associated with high concentrations of circulating catecholamines and it is possible that they increase Rsys through arteriolar α-adrenergic stimulation (Wasser and Jackson, 1991;Keiver and Hochachka, 1991;Keiver et al, 1992).…”
mentioning
confidence: 99%
“…This suggests that muscarinic ACh receptors are involved in hypoxia chemoreception and, by extension, that ACh is an important neurotransmitter in the initiation of the cardiovascular response to hypoxemia. These results are supported by previous studies on turtles and rattlesnakes, which found that injection of atropine eliminated the tachycardia normally seen during hypoxia exposure (Comeau and Hicks, 1994;Skovgaard et al, 2005). Injection of methysergide also blocked the effect of NaCN on f H (Fig.…”
Section: Cardiovascular Variablessupporting
confidence: 87%
“…Over half a century ago, anaesthetized snapping turtles (8-14 kg) were shown to demonstrate a large net L-R shunt, through the use of a dye-dilution technique (Steggerda and Essex, 1957). The presence of this pulmonary shunt has been more extensively described in red-eared slider turtles, Trachemys scripta (White and Ross, 1966;Comeau and Hicks, 1994;Hicks et al, 1996;Crossley et al, 1998;Overgaard et al, 2002b;Krosniunas and Hicks, 2003;Galli et al, 2004), and is attributed to low vagal tone and/or high adrenergic stimulation (Hicks, 1994;Hicks and Comeau, 1994;Hicks and Wang, 1998;Wang et al, 2001b;Overgaard et al, 2002b). Shunt ratio ( _ Q pul = _ Q sys ) is dependent on the relationship of pulmonary to systemic vascular resistance in turtles (Crossley et al, 1998).…”
Section: Fasted Measurementsmentioning
confidence: 99%